Curie temperature engineering in a novel 2D analog of iron ore (hematene) via strain. Issue 12 (22nd November 2020) - Singla, Renu; Hackett, Timothy A.; Kumar, Sarvesh; Sharma, Jyotsna; Kashyap, Manish K.
Abstract : Hematene: 3 atoms thick 2D material with high T C . Abstract : As a newly exfoliated magnetic 2D material from hematite, hematene is the most far-reaching ultrathin magnetic indirect bandgap semiconductor. We have carried out a detailed structural analysis of hematene via prefacing strain by means of first-principles calculations based on density functional theory (DFT). Hematene in the pristine form emerges out to be a magnetic semiconductor with a bandgap of 1.0/2.0 eV for the majority/minority spin channel. The dependence of magnetic anisotropy energy (MAE), T C, and the bandgap on compressive and tensile strains has been scanned exclusively. It is examined that T C depends firmly on the compressive strain and increases up to 21.1% at a compressive strain of 6% whereas it decreases significantly for tensile strain. The MAE is negatively correlated with the tensile and compressive strain. The value of MAE for all compressive strain cases is more than that of the pristine hematene. These results summarize that the studied 2D hematene has broad application prospects in spintronics, memory-based devices, and valleytronics.